2022
DOI: 10.4317/jced.59970
|View full text |Cite
|
Sign up to set email alerts
|

Association between orthodontic treatment and the occurrence of temporomandibular disorders: A systematic review and meta-analysis

Abstract: Background Temporomandibular disorders (TMD) are related to a series of clinical manifestations that appear in the form of pain. Currently, there is controversy about the appearance of TMDs after orthodontic treatment. Therefore, the objective of the present study was to determine the association between orthodontic treatment and the occurrence of Temporomandibular Disorders (TMD). Material and Methods A bibliographic search was carried out until April 2022, in the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…[30][31][32] However, other studies have indicated that orthodontic treatment does not decrease the risk of TMD. 16,18,33 Similarly, the literature shows that orthodontic treatment with or without tooth extraction does not increase the risk of TMD or worsen its pretreatment signs. 6,34 Our current data indicate that patients with sagittal asymmetry of occlusion had a high incidence of TMD.…”
Section: Discussionmentioning
confidence: 98%
“…[30][31][32] However, other studies have indicated that orthodontic treatment does not decrease the risk of TMD. 16,18,33 Similarly, the literature shows that orthodontic treatment with or without tooth extraction does not increase the risk of TMD or worsen its pretreatment signs. 6,34 Our current data indicate that patients with sagittal asymmetry of occlusion had a high incidence of TMD.…”
Section: Discussionmentioning
confidence: 98%
“…with certain studies indicating a potential correlation between orthodontic treatment and TMD. 44,45 Also, there exists scientific data indicating a possible association between TMD and the utilisation of intermaxillary elastics. 46 In some cases, intermaxillary elastic forces have the potential to impact the TMJ and potentially growth and development.…”
Section: Ta B L E 7 (Continued)mentioning
confidence: 99%
“…The references largely focus on the diagnosis, treatment, and management of TMD but do not offer explicit details regarding the length of TMD symptoms subsequent to the utilisation of intermaxillary elastics. 44,45,51,52 Hence, the assessment of the duration of intermaxillary elastic use was also conducted in our study. However, there were no significant differences identified in the remaining parameters, with the exception of the depression (PHQ-9) score.…”
mentioning
confidence: 99%
“…Conversely, many TMD experts hold opposing views, and various kinds of dental interventions, including routine orthodontic treatment, have been reported as causes of TMD [4,5].…”
Section: Introductionmentioning
confidence: 99%